STATE AND CHALLENGES FOR THE DIGITALIZATION OF AGRICULTURAL IN BULGARIA - N. Kostadinova (Trakia Journal of Sciences)
Digital agriculture in Bulgaria began its development in the last decade with the introduction of new technologies such as ground sensors, satellite imagery, GPS receivers in agricultural machinery and more. There are a number of companies in the country that create software products and applications aimed at the agricultural sector and especially at specific customers and according to their requierments. Software companies create web-based products and mobile applications for information visualization in order to control the work done and track activities on a farm. One of the priorities for the new programming period of the EU CAP is to improve the dissemination of knowledge, innovation and digitalisation in agriculture and rural areas, which will significantly contribute to increasing the competitiveness of the agricultural sector and will ensure a higher return on investment. The aim of this study is to examine the state and challenges of digitalization of the agricultural sector in Bulgaria. To achieve this goal, the following tasks are solved: to analyze the state of digitalization in Bulgarian agriculture; to identify trends in this area; to identify problems and challenges for the development of the agricultural sector in this direction.